Curcumin and normal functioning of joints: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (8th May 2017) - ; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Suomen Terveysravinto Oy, submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Finland, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to curcumin and normal functioning of joints. The food that is proposed as the subject of the health claim is curcumin. The Panel considers that curcumin is sufficiently characterised. The claimed effect proposed by the applicant is 'normal functioning of joints by reducing the biomarkers of inflammation'. The target population proposed by the applicant is the general population. Upon a request from EFSA to clarify whether the claimed effect is related to the normal function of joints or rather to the reduction of inflammation, the applicant did not address this issue in the reply. The Panel assumes that the claimed effect refers to the maintenance of joint function. The Panel considers that maintenance of joint function is a beneficial physiological effect. The Panel considers that no conclusions can be drawn from 15 human intervention studies conducted in patients with osteoarthritis or rheumatoid arthritis and from one study in obese subjects on serum cytokines for the scientific substantiation of the claim. In the absence of evidence for an effect of curcumin on the normal function of joints in humans, the results of the human studies on curcumin pharmacokinetics, safety and mechanistic studies, the animal studies and the in vitro studies submitted by the applicant cannot be used as a source of data for the scientific substantiation of the claim. The Panel concludes that a cause and effect relationship has not been established between the consumption of curcumin and maintenance of joint function.